Implementasi Prinsip-Prinsip Good Governance Dalam Meningkatkan Kinerja Organisasi Pelayanan Publik Pada Kelurahan Gundaling I Berastagi - Aprisca Paska Br Ginting; Bahrum Jamil; Yurial Arief Lubis (Universitas Medan Area, 2023)
Good governance has principles that are the basic keys in the implementation of good governance. At the Gundaling I Berastagi Village office the principles of good governance have not been fully implemented properly. This article aims to describe the implementation of good governance principles in Gundaling I Berastagi Village and to find out the inhibiting factors for the implementation of good governance principles in the Kelurahan. The problems in this study focused on the existence of public complaints against the discipline of employees in Gundaling I Berastagi Village. To approach this problem, Sedarmayanti's theoretical references are used, including responsiveness, effectiveness and efficiency, fairness, accountability and transparency. The data collected is based on data collection techniques through observation, interviews, and documentation. Then analyzed using a descriptive qualitative method. The results of the study indicate that the implementation of the principles of good governance in improving the performance of public service organizations at the Gundaling I Berastagi Village office has not been fully implemented properly because there are still indicators that have not gone well at the Gundaling I Berastagi Village Office.